2006
DOI: 10.1038/sj.jhh.1002120
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood pressure parameters and pulse wave velocity in normotensive and hypertensive subjects: invasive study

Abstract: Blood pressure (BP) is one of the most important contributing factors to pulse wave velocity (PWV), a classic measure of arterial stiffness. Although there have been many non-invasive studies to show the relation between arterial stiffness and BP, the results are controversial. The aim of this study is to evaluate the role of BP as an influencing factor on PWV using invasive method. We observed 174 normotensive and untreated hypertensive subjects using coronary angiography. Arterial stiffness was assessed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
117
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 44 publications
11
117
2
Order By: Relevance
“…For example, in 8 males the application of LBNP at −80 mm Hg or pre‐syncope threshold (group mean: −68 mm Hg) resulted in marked increases in cf‐PWV of ≈2.5 m/s, which related strongly to increases in low‐frequency power of systolic blood pressure,26 an indirect estimate of peripheral sympathetic outflow 43. However, although mean arterial pressure was unchanged during LBNP, this study noted trends for reductions in systolic blood pressure and failed to report pulse pressure changes,26 the strongest correlate of central PWV 10, 11. An examination of LBNP at 50% of maximum noted increases in cf‐PWV of 0.7 m/s, but these failed to reach statistical significance, most likely because of the small sample size.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…For example, in 8 males the application of LBNP at −80 mm Hg or pre‐syncope threshold (group mean: −68 mm Hg) resulted in marked increases in cf‐PWV of ≈2.5 m/s, which related strongly to increases in low‐frequency power of systolic blood pressure,26 an indirect estimate of peripheral sympathetic outflow 43. However, although mean arterial pressure was unchanged during LBNP, this study noted trends for reductions in systolic blood pressure and failed to report pulse pressure changes,26 the strongest correlate of central PWV 10, 11. An examination of LBNP at 50% of maximum noted increases in cf‐PWV of 0.7 m/s, but these failed to reach statistical significance, most likely because of the small sample size.…”
Section: Discussionmentioning
confidence: 59%
“…The difference in blood pressure responses between the pressure stimuli may highlight the critical need to maintain appropriate perfusion pressure in the face of blood loss (LBNP) but the benefit of increasing venous return and perfusion pressure (LBPP) during conditions such as exercise. Surprisingly, PWV did not change during LBPP despite the acknowledged pressure dependency 8, 9, 10, 11. We speculate that this could be the result of divergent effects of LBPP on mean blood pressure (distending) and pulse pressure (pulsatile) responses, or alternatively, that the small magnitude (≤4 mm Hg) changes in blood pressure are not sufficient to evoke detectable changes in PWV.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…7 Many investigators have confirmed that PWV was correlated with age, [8][9][10] systolic blood pressure (SBP), 11,12 and diastolic blood pressure (DBP). 11,13 Katsuda et al 14 demonstrated previously that PWV in the entire aorta (AoPWV) in young Kurosawa and Kusanagi-hypercholesterolemic (KHC) rabbits, an animal model of familial hypercholesterolemia 15 showed a slight (about 10%) but significant increase compared with that in age-matched control rabbits, and that SBP and DBP were also significantly higher in the KHC rabbit group than in the control group.…”
Section: Introductionmentioning
confidence: 98%